2021
DOI: 10.3390/s21217261
|View full text |Cite
|
Sign up to set email alerts
|

Combining Indoor Positioning Using Wi-Fi Round Trip Time with Dust Measurement in the Field of Occupational Health

Abstract: Monitoring of personal exposure to hazardous substances has garnered increasing attention over the past few years. However, no straightforward and exact indoor positioning technique has been available until the recent discovery of Wi-Fi round trip time (Wi-Fi RTT). In this study, we investigated the possibility of using a combination of Wi-Fi RTT for indoor positioning and a wearable particle monitor (WPM) to observe dust concentration during walking in a simulated factory. Ultrasonic humidifiers were used to … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…In the first stage, several criteria were initially applied to exclude studies, including those less than three pages in length, not written in English, articles that are not related to RFTs and VFTs. After this stage of the screening, 37 articles ([1], [2], [3] [8], [13], [14], [15], [16], [17], [19], [20], [21], [22], [23], [26], [27], [28], [29], [37], [39], [42], [44], [45], [49], [50], [51], [52], [55], [58], [59], [60], [61], [62], [63], [67], [68], [69]) were selected for full text assessment. The second stage of the screening process involved reading title, keywords, and abstract to identify studies that are relevant to RFTs and VFTs that had been peer reviewed in an educational context.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…In the first stage, several criteria were initially applied to exclude studies, including those less than three pages in length, not written in English, articles that are not related to RFTs and VFTs. After this stage of the screening, 37 articles ([1], [2], [3] [8], [13], [14], [15], [16], [17], [19], [20], [21], [22], [23], [26], [27], [28], [29], [37], [39], [42], [44], [45], [49], [50], [51], [52], [55], [58], [59], [60], [61], [62], [63], [67], [68], [69]) were selected for full text assessment. The second stage of the screening process involved reading title, keywords, and abstract to identify studies that are relevant to RFTs and VFTs that had been peer reviewed in an educational context.…”
Section: Methodsmentioning
confidence: 99%
“…Level of fear (1)(2)(3)(4)(5)(6)(7)(8)(9)(10) Student self-report at the start of the semester Student self-report at the end of the semester 1-2 According to the opinions of teachers who taught both theory and AR in the course, students significantly improved their practical welding skills during the course. The student's performance showed that AR helped students learning better.…”
Section: Fear Of Real Weldingmentioning
confidence: 99%
See 3 more Smart Citations